Risk factors for HIV infection among men who have sex with men in the ANRS IPERGAY PrEP trial. (18th October 2021) - Gras, Julien; Pillet, Marine; Antoni, Guillemette; Cua, Eric; Charreau, Isabelle; Raffi, F; Chidiac, Christian; Chas, Julie; Tremblay, Cécile; Spire, Bruno; Delaugerre, Constance; Meyer, Laurence; et al.
Abstract : Objectives: We aimed to assess among men who have sex with men (MSM) risk factors for HIV infection, to identify those who require urgent pre-exposure prophylaxis (PrEP) prescription. Methods: All participants enrolled in the placebo arm of the ANRS IPERGAY trial, or infected between screening and day 0, were included. Baseline characteristics were described and HIV incidence rate ratios (RRs) were estimated with their 95% CIs. Results: 203 MSM were included with a median follow-up of 9 months. During the study period, 16 participants acquired HIV infection while not receiving tenofovir disoproxil and emtricitabin (TDF/FTC) over 212.4 person-years (PYs) of follow-up (incidence rate 7.5/100 PYs, 95% CI: 4.3 to 12.2). Being enrolled in Paris was associated with a significant increased risk of HIV infection (RR: 4.1; 95% CI: 1.1 to 28.3). A high number of sexual partners in prior 2 months (≥10 vs < 5) and of condomless receptive anal sex episodes in prior 12 months (>5 vs <5) were strong predictors for HIV acquisition (RR: 10.6 (2 to 260.2) and 3.3 (1.2 to 10.2), respectively). Those who reported more often or only receptive sexual practices were also at increased risk (RR: 9.8 (2.0 to 246.6)). The use of recreational drugs in prior 12 months, especially gamma hydroxybutarate/gamma butyrolactone (RR: 5.9; 95% CI: 2 to 21.7), was associated with a significantly increased risk of HIV acquisition even after adjustment for sexual practices. Conclusions: MSM who have frequent condomless receptive anal sex and multiple partners, or use recreational drugs should be targeted in priority for PrEP prescription especially if they live in an area with a high prevalence of HIV infection.